Association of Mother’s Knowledge About Breast Milk nnd Breastfeeding With Exclusive Breastfeeding in Kecamatan Ilir Timur II Palembang.: Hubungan Pengetahuan Ibu Mengenai ASI dan Menyusui dengan Pemberian ASI Eksklusif di Kecamatan Ilir Timur II Palembang - Lestari, Puji; Kurniati, Ardesy meilizah; Mamun, Asmarani (Fakultas Kedokteran Universitas Sriwijaya, 2018)
Exclusive breasfeeding is defined as giving breast milk for infants from birth tosix months of age. The percentage of exclusive breastfeeding in Palembang hasnot reached national target. There aremany factors that may affect the mother in exclusive breastfeeding, one of which is mother's knowledge of breast milkand breastfeeding. The aim of this study was to examine the association of mother’s knowledge about breast milkandbreastfeeding with exclusive breastfeeding in Kecamatan Ilir Timur II Palembang. This cross-sectional study was held inJuly–December 2016. The population of this studywere mothers who have baby 6–24 months age in PuskesmasKecamatan Ilir Timur II. In this study, there were 93 mothers who fulfill inclusion criteria. The data were taken fromstructural interview by using questionnaire. The data were analyzed by Chi-Square statistic test using IBM SPSS Statistic22. The was no significant association of mother’s knowledge about breast milk and breastfeeding with exclusivebreastfeeding (p=0,120). The mother’s knowledge about breast milk and breastfeeding was not related with exclusivebreastfeeding in Kecamatan Ilir Timur II Kota Palembang.